Design and simulation of a high-power double-output isolated Cuk converter - Yasir M. Y. Ameen (PC Technology Center, 2021)
Among the transformer-less DC-DC converters, the superiority of the conventional Cuk converter is obvious in its good properties. However, the output power is limited for all transformer-less converter types including the conventional Cuk converter. In order to get more supplied power from this converter, some changes in its design were necessary. One of these modifications is to add a transformer to transfer more power and to separate the output side from the input side. Supply of some applications such as the DC link of modular multilevel inverters, e. g. cascaded H-bridge (CHB) topologies required more than one output. Hence, this paper is concerned with the design, analysis and simulation of an isolated dual-output modified Cuk converter. The proposed converter is designed to deliver a total output power of 2,000 W using only one modulating switch. A complete design and detailed analysis of the high-frequency transformer with the ANSYS Maxwell platform is presented in this paper. The modeling and simulation results of the high-frequency transformer are validated by the experimental implementation results and good agreement was obtained with a small percentage of errors less than 4 %. A set of analytical equations has been derived and presented in this paper to represent a mathematical model of the converter. In addition, the entire converter circuit was simulated and analyzed with MATLAB/Simulink. The simulation results were checked and compared to the findings of the mathematical model, yielding an excellent match with a percentage error of less than 2.15 %. Finally, when the presented converter was tested under various loads, including unbalanced load situations, a reasonable output voltage regulation was achieved, with the two output voltages being nearly identical with a deviation of less than 0.25 % under a severe unbalanced load condition of 150 %